Interactions between physical activity and the environment to improve adolescent self–esteem: a randomised controlled trial. (9th February 2015) - Wood, C.; Sandercock, G.; Barton, J.
Natural environments promote physical activity (PA) and are psychologically restorative. In adults, performing PA in nature provides additive benefits for self–esteem (SE). Studies in adolescents indicate no such effect. However, they have not examined the effect of interaction with natural environments. The aim of this study was to analyse the effects of exercising in natural and built environments on adolescent PA and SE. Sixty adolescents participated in a natural and built orienteering course in a randomised order. PA was assessed throughout whilst SE was assessed pre– and post–intervention. There was a significant effect for PA due to environment (P < 0.001) and sex (P < 0.01). Almost half the time in the natural environment was spent in moderate to vigorous PA, compared to a quarter in the built. The PA significantly improved SE (P < 0.05); however there was no environmental effect (P > 0.05). Natural environments should be used as a tool for engaging adolescents in PA.